Generative AI and the Development of Adaptive Islamic Education Teaching Materials for 21st Century Learning - Najwa Sajida El Yunusi; Moh Rieza Salmany; Ahmad Jawahirun Ni’am Fikry; Mashuda Mashuda; Imam Syafi’i; Munawir Munawir (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2026)
The rapid development of Generative Artificial Intelligence (Generative AI) has created new opportunities for developing more adaptive and personalized teaching materials in 21st-century learning. In the context of Islamic Religious Education (IRE), this technology is essential for addressing diverse student needs while fostering critical thinking, creativity, communication, collaboration, and digital literacy skills. This article aims to analyze the role of Generative AI in developing adaptive IRE teaching materials and its relevance to 21st-century learning. The study employed a qualitative approach using a library research method through the analysis of relevant academic journals, books, and scholarly documents. The findings indicate that Generative AI can support personalized learning content, multimodal instructional materials, and flexible assessment development tailored to students’ characteristics. However, its implementation also presents challenges, including the risk of religious misinformation, technological dependency, academic plagiarism, and the weakening of spiritual and humanistic dimensions in learning. Therefore, teachers remain essential as facilitators, value validators, and pedagogical guides to ensure that AI utilization remains aligned with Islamic values and educational objectives